Mobilização dos saberes curriculares em ambiente virtual de ensino-aprendizagem - Souza, Eliane Kiss de (2007)
We propose to assess the mobilization of knowledge, concerning the syllabus taught at High School Level in the *Normal *Course* *(the Brazilian course to prepare primary teachers) using a platform called AMEM (*Ambiente Multimídia para Educação Mediada por Computador *a "Multimedia Environment for Computer- Mediated Education"). As an investigative strategy we will use schoolar action research, focusing on professional autonomy and the problematization of knowledge in the educational practice, as well as the transition of common knowledge to scientific knowledge, as in the subject of General Didactics, articulating the theoretical and practical dimensions. In this process of spiral-shaped cycles, we will attempt to improve AMEM and the mobilization of knowledge in the syllabus of this teaching modality